METODE BERCERITA DALAM MENGEMBANGKAN BAHASA MELALUI PENDIDIKAN SENI PADA GURU-GURU PAUD/TK DI WILAYAH I ACEH BESAR - Andika, Benni - (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2023)
The purpose of this research is to use a storytelling method to develop early childhood language through art education for PAUD/Kindergarten teachers in Region I, Aceh Besar District. Art education is very important in developing children's knowledge of art in Indonesia and especially in Aceh Besar through teachers. Art must be taught to children from an age they are still considered young in order to increase their knowledge of the development of art from an early age. The research was conducted using qualitative methods with a focus on case study research. According to Robert K Yin, a case study will focus more on or attempt to answer how and why questions, and at a certain level also answer what/what questions in research activities. This research is useful to see; (1) The child's ability to identify something in art education through learning the storytelling method (2) Knowing the level of validity and practicality of developing the Storytelling method and improving language skills in children. (3) The teacher's ability to provide learning for children by using a good storytelling method.